2020
DOI: 10.1177/2325967120964481
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sleep Is an Independent Predictor of In-Season Injury in Male Collegiate Basketball Players

Abstract: Background: Although decreased sleep has been associated with decreased performance, increased illness risk, and impaired well-being in athletes, the relationship between sleep and injury risk in collegiate athletes is unknown. Purpose/Hypothesis: To evaluate the independent effects of sleep duration and subjective well-being on in-season injury in male collegiate basketball athletes. We hypothesized that decreased sleep would be associated with an increased risk of in-season injury. Study Design: Cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
2
22
1
Order By: Relevance
“…Our findings that well-being and injury risk are related also are in line with findings from our previous study in collegiate male basketball players, where it was found that subjective well-being variables were significant predictors of injury. 34 Our findings differ slightly, however, in that while that study found that soreness in male athletes was the only independent subjective well-being metric predictive of injury after adjusting for sleep duration, we found that both soreness and mood were independent predictors of injury in female athletes in the multivariable models. Nonetheless, the finding that worse subjective well-being is correlated with higher incidence of injury is consistent with prior research exploring this relationship.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings that well-being and injury risk are related also are in line with findings from our previous study in collegiate male basketball players, where it was found that subjective well-being variables were significant predictors of injury. 34 Our findings differ slightly, however, in that while that study found that soreness in male athletes was the only independent subjective well-being metric predictive of injury after adjusting for sleep duration, we found that both soreness and mood were independent predictors of injury in female athletes in the multivariable models. Nonetheless, the finding that worse subjective well-being is correlated with higher incidence of injury is consistent with prior research exploring this relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are consistent with previous studies in elite athletes that found that decreases in sleep volume contribute to a higher risk of injury. 18 , 29 , 34 Specifically, we sought to reproduce previously published findings related to well-being and injury risk regarding collegiate men’s basketball athletes. With respect to sleep duration, our results are very similar, suggesting that these findings may be generalizable to other populations of collegiate athletes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep deprivation can also harm cognitive functions like such as judgement and decision-making; increase the risk of exercise-related injurie; allow for the development of recurrent upper airway infections and cause chronic pain; even lead to the creation of a vicious cycle related to sleep loss, impaired recovery; increased feelings of pain that themselves predispose athletes to sleep disturbances and delay recovery from a sports-related injury e.g. a concussion [10,13,[23][24][25][26]. The present study supports the earlier findings that sleeping-related problems are indisputably common among professional athletes [1,6].…”
Section: Discussionmentioning
confidence: 99%